GENERAL QUESTIONS AS TO PROVIDING ELECTROMAGNETIC COMPATIBILITY OF POWER CABLE LINES, THEIR AMPERAGE CAPACITY AND TYPES OF SHIELD CONSTRUCTION - I.A. Kostiukov (National Technical University "Kharkiv Polytechnic Institute", 2013)
Works studying ways of reducing magnetic fields of cross-linked polyethylene power cable lines are reviewed. Different aspects of single-phase power cable shield construction influence on thermal conditions of a three-phase power cable line are analyzed. Questions concerning electromagnetic compatibility of power cables are considered.